Interrelasi Islam dan Politik - Hidayatulloh, Muhammad Syarif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The issue of the relationship between religion and politics is an old issue in modern human history, both of which always spark polemics regarding the position of religion in the political arena which, at least, involves two groups that are diametrically opposed. One party is campaigning for religion to be included in every political consideration. This idea is known as theocracy, a religion-based government. As a consequence, religion becomes the highest umbrella in every political policy. On the other hand, there are parties who actually reject religious interference in political affairs. Religion must be excluded from public discourse and understood as a private matter that only concerns individual interests. Religion is nothing more than a ritual affair that describes man's dependence on his god.